(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2021)
Bearing is an important part in the pump so that the monitoring of the bearing condition must be carried out continuously to prevent damage to propagate in other parts that can cause increased of maintenance costs. One of the best technique to detect early fault of bearing is by method of enveloping vibration spectrum analysis which produced by the vibrating of bearing with a frequency range of 60 - 60,000 CPM where the frequency of damage such as BPFI, BPFO, BSF and FTF are found between these frequencies. Overall technique is used to monitor the movement of the increase in the amount of the amplitude to be adapdetd based on the vibration severity chart by the SKF standard. The study was conducted by taking the vibration signal by the SKF microlog analyzer produced by 7314 BECBM series bearing at a speed of 2980 Rpm. The next step is to analyze the enveloping spectrum by the SKF aptitude analyst software. The results showed that bearing with natural defect conditions had the characteristic of producing peak frequency amplitudes coinciding with the impulse frequency lines of each BPFI of 0.26 gE, BPFO of 0.20 gE. In BSF and FTF there were no significant peak amplitudes found around the bearing defect frequency. In new bearing in good condition, the enveloping spectrum characteristics where the peak amplitude does not appear and coincide with the frequency of the bearing defect frequencies BPFI, BPFO, BSF and FTF. On the overall vibration signal it was found that the magnitude of 2,819 gE was in the satisfactory category but it was found that the bearing was in defect condition.